Kebangkitan Nasional: Pemuda Melawan Pandemi Global - Roma Doni Azmi; Rizqon Halal Syah Aji (ADALAH, 2020)
AbstractThe commemoration of National Awakening Day in the midst of the Covid-19 Pandemic has a special meaning for Indonesian young people. Youth groups become seriously affected objects because of the global Pandem outbreak. They are affected in the economic, health, education and socio-cultural aspects. As the successors to the nation's patriotism, young people must be the pioneers in a joint effort in fighting the crisis because of the impact of Covid-19. Indonesia, as one of the affected countries, has great power, young people as energy pioneers in the struggle against the pandemic. The Ethics of National Awakening by youth, is the right momentum to assist the government in developing a measured and systematic strategy, making Indonesian youth and all elements of the Nation survive and immediately emerge from the impact of the global pandemic.Keywords: National Revival, Global Pandemic, Youth, Economic Change, Indonesia AbstrakPeringatan hari Kebangkitan Nasional di tengah Pandemi Covid-19 mempunyai makna khusus pada diri pemuda Indonesia.  Kelompok pemuda menjadi objek yang terdampak serius karena wabah Pandem global.  Mereka terdampak pada aspek ekonomi, kesehatan, pendidikan hingga sosial budaya. Sebagai penerus patriotisme bangsa, para pemuda harus menjadi pelopor dalam usaha bersama dalam upaya melawan krisis karena dampak Covid-19. Indonesia, sebagai salah satu negara terdampak, memiliki kekuatan besar kaum muda sebagai energi pelopor pergerakan dalam melawan pandemi. Etos Kebangkitan Nasional oleh pemuda, merupakan momentum yang tepat untuk membantu pemerintah dalam menyusun strategi yang terukur dan sistematis, sehingga pemuda Indonesia serta seluruh elemen Bangsa dapat survive dan segera keluar dari dampak pandemi global.Kata Kunci: Kebangkitan Nasional, Pandemi Global, Pemuda, Dampak Ekonomi, Indonesia